Investigating the management of alcohol‐related presentations in an Australian teaching hospital. (7th February 2019) - Qian, Siyu; Irani, Mudar; Brighton, Renee; Yeo, Wilfred; Reid, David; Sinclair, Barbara; Bresnahan, Susan; Lynch, Peter; Feng, Xiaoqi; Yu, Ping
Abstract: Introduction and Aims: Alcohol‐related morbidity is estimated to range from 10–38% of the presentations to hospital emergency departments. This study aims to investigate the actual management process for alcohol‐related presentations in a teaching hospital in Australia. Design and Methods: Retrospective audit was conducted on the electronic medical records of 210 presentations with a primary or secondary diagnosis of 'alcohol use disorder' at discharge between November 2016 and February 2017. Six key management steps were investigated: identification of alcohol use disorder, documentation, thiamine, alcohol withdrawal assessment, benzodiazepine for alcohol withdrawal and referral to the drug and alcohol consultation liaison service. Results: Of all the 210 presentations, 77.1% (162) were identified with alcohol use disorder in the initial assessments; 64.3% (135) were documented with alcohol use history, 49.5% (104) were prescribed with thiamine, 48.1% (101) were assessed with the alcohol withdrawal scale, 41% (86) were prescribed with benzodiazepine for alcohol withdrawal and only 38.6% (81) were referred to the drug and alcohol consultation liaison service. Only 8.6% (18) of the initial presentations were directly related to alcohol. These presentations had a higher completion rate in each of the six steps than those (91.4%, 192) not directly related to alcohol. Only 6.2% (13) were formally screened for alcohol use. Discussion and Conclusions: The findings suggest a need to improve the alcohol management practice in the hospital. Routine use of an alcohol screening tool can enable early identification of the alcohol use disorder and to improve the management of this problem in the hospital.